In Vitro and In Vivo Gene Delivery by Recombinant Baculoviruses - Tani, Hideki (American Society for Microbiology, 2003)
Although recombinant baculovirus vectors can be an efficient tool for gene transfer into mammalian cells in vitro, gene transduction in vivo has been hampered by the inactivation of baculoviruses by serum complement. Recombinant baculoviruses possessing excess envelope protein gp64 or other viral envelope proteins on the virion surface deliver foreign genes into a variety of mammalian cell lines more efficiently than the unmodified baculovirus. In this study, we examined the efficiency of gene transfer both in vitro and in vivo by recombinant baculoviruses possessing envelope proteins derived from either vesicular stomatitis virus (VSVG) or rabies virus. These recombinant viruses efficiently transferred reporter genes into neural cell lines, primary rat neural cells, and primary mouse osteal cells in vitro. The VSVG-modified baculovirus exhibited greater resistance to inactivation by animal sera than the unmodified baculovirus. A synthetic inhibitor of the complement activation pathway circumvented the serum inactivation of the unmodified baculovirus. Furthermore, the VSVG-modified baculovirus could transduce a reporter gene into the cerebral cortex and testis of mice by direct inoculation in vivo. These results suggest the possible use of the recombinant baculovirus vectors in combination with the administration of complement inhibitors for in vivo gene therapy.